On screen writing - Dmytryk, Edward (Routledge, Taylor & Francis Group, 2019)
"With On Screen Writing, director Edward Dmytryk offers a clear, methodical overview of the needs, practices, and problems of screenwriting, including extensive coverage of adaptation. Written In an informal, anecdotal style and using script examples from Hollywood classics, Dmytryk presents a practical set of principles for writing engaging, filmable screenplays. Originally published in 1985, this reissue of Dmytryk's classic screenwriting book includes a new critical introduction by Mick Hurbis-Cherrier, as well as chapter lessons, discussion questions, exercises, and a glossary"--